Acetylation Modification During Autophagy and Vascular Aging - Sun, Jiaxing; Tai, Shi; Tang, Liang; Yang, Hui; Chen, Mingxian; Xiao, Yichao; Li, Xuping; Zhu, Zhaowei; Zhou, Shenghua (Frontiers in Physiology, 2021)
Vascular aging plays a pivotal role in the morbidity and mortality of elderly people. Decrease in autophagy leads to acceleration of vascular aging, while increase in autophagy leads to deceleration of vascular aging. And emerging evidence indicates that acetylation plays an important role in autophagy regulation; therefore, recent research has focused on an in-depth analysis of the mechanisms underlying this regulation. In this review, current knowledge on the role of acetylation of autophagy-related proteins and the mechanisms by which acetylation including non-autophagy-related acetylation and autophagy related acetylation regulate vascular aging have been discussed. We conclude that the occurrence of acetylation modification during autophagy is a fundamental mechanism underlying autophagy regulation and provides promising targets to retard vascular aging.